ALLERGIC RHINITIS AND MENTAL HEALTH: EPIDEMIOLOGICAL ASSOCIATIONS AND NEUROIMMUNE MECHANISMS - Rogulski, Krzysztof; Szczepański, Piotr; Kącikowska, Justyna; Grzelak, Oliwia; Bolek, Oliwia; Majkowska, Magdalena; Fengier, Maria; Kuśmierczyk, Weronika; Sordyl, Katarzyna; Trzaskowski, Jakub (International Journal of Innovative Technologies in Social Science, 2026)
Allergic rhinitis (AR) is a common chronic condition associated with significant quality-of-life impairment. In recent years, increasing attention has been directed toward the potential relationship between AR and mental health outcomes. Epidemiological studies have reported associations between AR and a range of psychological conditions, including depression, anxiety, sleep disturbances, and impaired cognitive performance.Emerging evidence from psychoneuroimmunology provides several potential mechanisms that may explain these relationships. Peripheral allergic inflammation may influence central nervous system function through cytokine-mediated immune–brain communication, histaminergic signaling, alterations in blood–brain barrier permeability, and neuroendocrine responses related to stress. In addition, sleep disturbances caused by nasal obstruction and inflammatory mediators may represent an important intermediary pathway linking allergic symptoms with mood and cognitive changes.This narrative review summarizes current evidence on the epidemiological associations between allergic rhinitis and mental health outcomes and discusses potential neuroimmune mechanisms underlying these interactions. Understanding these complex relationships may contribute to a more comprehensive approach to the management of allergic rhinitis and highlight the importance of considering psychological and sleep-related factors in affected patients.